Clinical and subclinical intestinal inflammation assessed by the mucosal patch technique: studies of mucosal neutrophil and eosinophil activation in inflammatory bowel diseases and irritable bowel syndrome. Issue 12 (11th November 2004) - Kristjánsson, G; Venge, P; Wanders, A; Lööf, L; Hällgren, R
Abstract : Background and aims: There is a clear need for a rapid, simple, safe, and sensitive method of determining the type and intensity of inflammation in the gut mucosa in clinical practice. In this study, we have evaluated the potential of a new method, the mucosal patch technique, in patients with and without apparent gut inflammation, as assessed by conventional diagnostic procedures. Subjects and methods: The technique tested is based on the idea that inflammatory mediators released from the rectal mucosa can be absorbed by and then extracted from cellulose patches brought into contact with the mucosa by use of an instrument with an inflatable balloon. Measurements were performed in healthy controls (n = 16) and in patients with active (n = 19) and inactive ulcerative colitis (UC, n = 8), collagen colitis (CC, n = 12), coeliac disease (n = 13), and irritable bowel syndrome (IBS, n = 13). Results: Inflammatory mediators from neutrophils (myeloperoxidase (MPO)) and eosinophils (eosinophil cationic protein (ECP)) were increased on average 300- and 10-fold, respectively, in patients with active UC compared with healthy controls and were correlated with the endoscopic score. Patients with inactive UC, CC, coeliac disease, and IBS exhibited no endoscopic signs of inflammation. These patient groups had significantly lower levels of MPO and ECP than the active UC group but showed on average a four- to sevenfold increase in MPO compared with healthy controls. Conclusion: The mucosal patch technique was well tolerated by patients and easily applied by the investigator. Pronounced neutrophil and eosinophil involvement in UC was demonstrated. With the high sensitivity of the technique, low degree mucosal neutrophil activation could also be quantified in patients with CC and UC in clinical remission. The finding of increased neutrophil involvement in patients with IBS contributes to the pathophysiological ideas of this disease.